2023
DOI: 10.3389/froh.2023.1170966
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise therapy on pain relief and jaw mobility in patients with pain-related temporomandibular disorders: a systematic review

Akiko Shimada,
Toru Ogawa,
Sara Reda Sammour
et al.

Abstract: BackgroundOrofacial pain conditions are complex disorders that involve biological, social, and psychological factors. Temporomandibular Disorders (TMDs) are one of the most common orofacial pain conditions, and our previous literature review indicated that exercise therapy has shown promise in reducing TMD-related pain. However, more evidence is needed to firmly establish its effectiveness.ObjectivesThis systematic review aims to investigate the effectiveness of exercise therapy on pain relief and jaw mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Among the also non-surgical methods used to treat TMJ physiotherapy, kinesiotaping, biofeedback [ 37 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the also non-surgical methods used to treat TMJ physiotherapy, kinesiotaping, biofeedback [ 37 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has shown that Low-level laser therapy (LLLT) is effective in relieving pain and improving functional outcomes in patients with TMJ [ 40 , 41 ]. Popularity is the use of a LLLT that penetrates the skin with a wavelength of 904 nm and a frequency of 700 Hz to a depth of 30 mm.…”
Section: Introductionmentioning
confidence: 99%